The problematic American experience with deferred corporate prosecutions. Issue 1 (2nd January 2019) - Rakoff, Jed S.
Abstract : Australia is in the process of implementing a significant change to prosecutorial strategy through the Crime Legislation Amendment (Combatting Corporate Crime Bill) 2017 . This will allow for the introduction of Deferred Prosecution Agreements, designed to encourage early self-reporting of misconduct in return for a deferral of punishment as long as agreed restrictions are complied with. It remains subject to consultation following the release of a draft Deferred Prosecution Agreement Code of Practice. The mechanism has been used extensively in the United States and in the United Kingdom. In this article, based on extensive experience adjudicating on the DPA experience in the United States, I argue that policymakers should exercise caution. While the DPA mechanism generates headlines it also facilitates the façade of enforcement.